Tural phenomenon of Monument Building in Batak Toba People Life in Pangururan District and Palipi District Samosir - Ulung Napitu; Corry Corry; Resna Napitu; Supsiloani Supsiloani (Budapest International Research and Critics University, 2020)
This study aims to analyze the phenomenon of monument building culture in the life of Toba Batak tribe in Pangururan and Palipi Districts, Samosir Regency. This research uses descriptive analytic method with phenomenology approach. The phenomenological approach is a tradition of qualitative research that is rooted in philosophical and psychological, and focuses on the experience of human life (sociology). The results of this study indicate that the cultural phenomenon of monument building in the life of Toba Batak community is a form of cultural activity carried out by Toba Batak tribe as a tribute to the spirits of the ancestors or to the Ompu-Ompu, on the basis of religion and tradition that are still alive until now. This is Toba Batak tribe who highly respects the spirits of their ancestors.